QoS and energy management in cognitive radio network : case study approach - Mishra, Vishram; Mathew, Jimson; Lau, Chiew-Tong (Springer, 2017)
This book covers the important aspects involved in making cognitive radio devices portable, mobile and green, while also extending their service life. At the same time, it presents a variety of established theories and practices concerning cognitive radio from academia and industry. Cognitive radio can be utilized as a backbone communication medium for wireless devices. To effectively achieve its commercial application, various aspects of quality of service and energy management need to be addressed. The topics covered in the book include energy management and quality of service provisioning at Layer 2 of the protocol stack from the perspectives of medium access control, spectrum selection, and self-coexistence for cognitive radio networks.
Keywords: Cognitive radio networks.; elektronické knihy; electronic books